(untitled) (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
PhD (in Philology), Associate Professor Lomakina I. Reinterpretations of Argentine folklore in Ukrainian: Gato, Samba, and Chacarera